Religious pilgrimage and COVID-19. An observational report in Italy from contact tracing activities: Emanuela Maria Frisicale. (25th October 2022) - Ferraro, F; Frisicale, EM; Rapiti, A; Marotta, C; Bonfigli, S; Angeloni, U; Maraglino, F; Rezza, G
Abstract: Issue/Problem: Religious Mass Gathering (MG) represent one of public health challenges for Health Authorities due to potential spread of communicable diseases. This is much more true during a pandemic as COVID-19. Surveillance is crucial to prevent further spreading of infectious disease related to a religious MG. Description of the problem: During international contact tracing activities an increase of reporting of COVID-cases with a travel history to a Catholic shrine in Europe was observed, despite travel restrictions put in place. In order to promote public health actions as risk communication, a risk evaluation was conducted. A descriptive analysis was carried out: personal and vaccination data were collected; for cases, date and type of positive tests, date of symptoms' onset were collected; for high-risk contacts, date and type of negative tests at the end of follow-up were collected. Frequencies were calculated. Results: Six journeys back from Medjugorje were identified, with at least one positive case. All trips took place between 18/09/2021 and 29/10/2021. 31 positive cases out of 160 travellers were identified, with number of cases per travel ranging from 1 to 11. Lessons: Religious MG represent an important global health issue. Even though a specific surveillance was not activated, international contact tracing activities turned out a great source of epidemic intelligence and consequent surveillance and control activities led to risk assessment and communication actions. Key messages: In the pandemic context, where travel restrictions were put in place, surveillance for Religious MG should be always implemented. Cooperation among all the stakeholders involved as Church, travel agency, Regional Health Systems and Government Bodies has to be promoted for specific surveillance in religious MG events.